Geology of Casino porphyry copper-molybdenum deposit, Dawson Range, Y.T. ... - Godwin, Colin Inglis (University of British Columbia, 2010)
Casino porphyry copper-molybdenum deposit ia in the Dawson Range, midway between Dawson City and Whitehorse, Y.T. Mid-Cretaceous granitic rocks of the Klotassin batholith form the backbone of the Dawson Range and have intruded the Yukon Hetamorphic Complex of Paleozoic or earlier age. A 70 m.y. old volcanic unit, the Casino complex, intruded the Klotassin batholith, and is cogenetic with Casino deposit. Hear the deposit extrusive volcanic rocks are unknown but formation of a subvolcanic plug of feldspar porphyry was followed by an explosive event that formed a steeply plunging, conical breccia pipe. This permeable pipe, about 2,000 ft. (670m.) by 1,200 ft. (400m.) at the surface localized hydrothermal fluids that formed large concentrically zoned alteration patterns during upward and outward percolation. A potassic alteration facies core, about 1,500 ft. (500m.) in diameter, is centered approximately on the breccia pipe, and is characterized by secondary magnetite, biotite and potassium feldspar. This core ...